(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Water is the most widely consumed commodity on the planet. Water on Earth comes in a variety of forms. India has 17% of the world’s population but just 4% of the world’s water resources, 80% of which are utilized for agriculture. Water consumption in India’s cities is about 40%, causing ground water tables to plummet below 2 to 3 meters per year.